PENGARUH PENERAPAN SISTEM PENGENDALIAN INTERNAL PEMERINTAH DAN KEPATUHAN SISTEM AKUNTANSI PEMERINTAH TERHADAP AKUNTABILITAS KINERJA DENGAN KUALITAS LAPORAN KEUANGAN SEBAGAI INTERVENING (Studi Kasus di Pemerintah Kabupaten Lumajang Jawa Timur ) - Harfiahani Indah Rakhma Ningtyas ; Dr. Roekhudin, Ak., CSRS., CA Dr. Wuryan Andayani, Ak
The purpose of this study is to analyze the influence of Government Internal Control System (SPIP) and Government Accounting Standard (SAP). This quantitative study uses primary data. Sound performance accountability enhances the performance of government officials in providing services for the public. The result of this study proves that SPIP and SAP influence the financial report quality of Lumajang regency government. _x000D_ The quality of financial report is determined by the quality of human resource, which in turn improves performance that increases the performance accountability of Lumajang regency government. SPIP does not directly influence performance accountability